Commutability and concordance of four hepatitis B virus DNA assays in an international multicenter study. (August 2017) - Maasoumy, Benjamin; Bremer, Birgit; Lehmann, Patrick; Marins, Ed G.; Michel-Treil, Véronique; Simon, Christian O.; Njoya, Merlin; Cornberg, Markus; Paxinos, Ellen; Manns, Michael P.; Vermehren, Johannes; Sarrazin, Christoph; et al.
Background: HBV DNA is the most important molecular marker in hepatitis B, used to determine treatment indication and monitoring. Most patients require lifelong hepatitis B virus (HBV) management, thus viral load (VL) monitoring may be performed at different laboratories, with different HBV assays, which may result in different VL results. This multicenter study compares the commutability and concordance of results from four different HBV DNA assays: CAP/CTM HBVv2, HPS/CTM HBVv2 and the new cobas 6800/8800 HBV and cobas 4800 HBV assays. Methods: Across all four assays, HBV limit of detection (LoD) and linearity at lower concentrations were assessed using panels traceable to the World Health Organization international standard, and concordance was investigated at the important medical decision cutoffs 2000 and 20, 000 IU/ml, using specimens from HBV-positive patients. Results: The calculated LoD via a probit curve was 2.7 IU/ml for cobas 6800/8800 HBV, 2.8 IU/ml for cobas 4800 HBV, 9.6 IU/ml for CAP/CTM HBVv2, and 6.2 IU/ml for HPS/CTM HBVv2. The average accuracy was comparable between cobas 6800/8800 HBV, cobas 4800 HBV and CAP/CTM HBVv2 (0.04–0.05 log10 IU/ml), while a slightly lower accuracy was documented for HPS/CTM HBVv2 (−0.16 log10 IU/ml). A total of 211–245 clinical samples were used for a pairwise comparison. Mean paired log differences ranged from −0.17 log10 IU/ml to −0.01 log10 IU/ml. Coefficient of determination was over 98% for all pairs with high overall percent agreement at the 2000 and 20, 000 IU/ml cutoffs (from 91.7% to 96.3%). In a subset of samples with VL±0.5 log10 to the 2000 and 20, 000 IU/ml thresholds, concordance was still 72% and 82%, respectively. Conclusions: The new cobas 6800/8800 HBV and 4800 HBV assays show high accuracy in samples with low-level viremia and a high concordance with the established HBV tests, CAP/CTM HBVv2 and HPS/CTM HBVv2, at 2000 and 20, 000 IU/ml. Thus, all four HBV assays have high commutability and may be used interchangeably in routine clinical practice.